Anti Irritant Activity of Extract from the Aerial Parts of Echinops echinatus Compositae: Anti Irritant Activity of Echinops echinatus - Zaheer, Muhammad; Hussain, Naqi; Rahman, Salma; Rehman, Sajid-ur- (Biological Sciences - PJSIR, 2012)